2018
DOI: 10.1002/mgg3.471
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between urinary glycosaminoglycan levels and phenotypes of mucopolysaccharidoses

Abstract: BackgroundThe aim of this study was to use the liquid chromatography/tandem mass spectrometry (LC‐MS/MS) method to quantitate levels of three urinary glycosaminoglycans (GAGs; dermatan sulfate [DS], heparan sulfate [HS], and keratan sulfate [KS]) to help make a correct diagnosis of mucopolysaccharidosis (MPS).MethodsWe analyzed the relationships between phenotypes and levels of urinary GAGs of 79 patients with different types of MPS.ResultsThe patients with mental retardation (n = 21) had significantly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 39 publications
1
24
0
1
Order By: Relevance
“…The relationships between uGAG-derived disaccharide levels, including DS and HS and the severity of the phenotype, were investigated, and the values of DS and HS closely matched the phenotypes of MPS. The MPS II patients with mental retardation had significantly higher levels of HS than those without mental retardation, and the DS values in the MPS II patients with hernia, hepatosplenomegaly, claw hands, coarse face, valvular heart disease, and joint stiffness were higher than in those without the symptoms reported by Lin et al [42]. In the current study, "positive" uGAG tests indicated that the Dimethylmethylene Blue/creatinine (DMB/Cre.)…”
Section: The Quantitative Analysis Of Urinary Gag-derived Disaccharidsupporting
confidence: 56%
“…The relationships between uGAG-derived disaccharide levels, including DS and HS and the severity of the phenotype, were investigated, and the values of DS and HS closely matched the phenotypes of MPS. The MPS II patients with mental retardation had significantly higher levels of HS than those without mental retardation, and the DS values in the MPS II patients with hernia, hepatosplenomegaly, claw hands, coarse face, valvular heart disease, and joint stiffness were higher than in those without the symptoms reported by Lin et al [42]. In the current study, "positive" uGAG tests indicated that the Dimethylmethylene Blue/creatinine (DMB/Cre.)…”
Section: The Quantitative Analysis Of Urinary Gag-derived Disaccharidsupporting
confidence: 56%
“…The "skeletal" group is caused by KS and includes MPS IVA, with manifestations of joint laxity, odontoid hypoplasia, genu valgum, extreme short stature, and skeletal dysplasia. The amounts of the affected GAG-derived disaccharides have been associated with the clinical presentations, onset, and severity of MPS disorders [25][26][27][28]. Settembre et al [29] reported that GAG accumulation in lysosomes disrupts autophagy, which is important for chondrocyte metabolism during endochondral ossification, leading to chondrocyte viability and thus the development of skeletal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Total urine GAGs concentrations have been used in the Phase II/III trials as markers of the biochemical efficacy of ERT [17][18][19]21,22,30,31,33] and their level can be correlated with the different severity of phenotypes [118,119]. Their decrease is dramatic in the first 6-12 months of treatment and is sustained over the years tending to normalize in almost all patients [29,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Gags and Other Possible Biomarkersmentioning
confidence: 99%